A comparative study on turbulent models for three-dimensional thermo-hydrodynamic analysis of textured thrust bearing - Tauviqirrahman, Mohammad; Lim, Youngbin; Jamari, Jamari; Muchammad, Muchammad; Pugastri, Ben Oni; Yohana, Eflita; Ammarullah, Muhammad Imam (Cogent engineering, 2024)
Various studies have been conducted to improve the tribological performance of thrust bearings. In the present study, thermohydrodynamic (THD) analysis was carried out to explore the performance of textured thrust bearings with rectangular dimples in three dimensions, considering turbulence and cavitation. Various models are available for predicting turbulence. Owing to disparities in forcing viscosity, velocity fluctuation, and parameter estimation, the performance of these models is typically distinct. Model comparison is the simplest method for identifying the strengths, limitations, and sources of uncertainty in a model. In this study, the k-ω turbulence model was of particular interest. Four k-ω models, namely, the standard k-ω model, BSL (Baseline) k-ω model, SST (shear-stress transport) k-ω model, and GEKO (Generalized k-Omega) k-ω model, were evaluated to predict the bearing characteristics. In this study, not only the tribological performance but also the acoustic characteristics were investigated. To capture more realistic phenomena, a multiphase mixture cavitation model was used to analyze the cavitation behavior of the lubricant. The results of this study show a comparison of the tribological performance between each turbulence model while considering the presence of cavitation and thermal conditions on the thrust bearing. In addition, the performance of thrust bearings under laminar flow conditions without cavitation was compared with these results. By comparing the various models, the necessity of incorporating turbulence and cavitation-coupled effects was confirmed. The main results also show that in the case of the BSL and standard k-ω turbulence models.